Phytoplankton data in Lake Erken, 1989-2011 - Phytoplankton data in Lake Erken 1989-2011 - Erken Laboratory, Uppsala University (Uppsala University, 2018)
Phytoplankton biomass data from Lake Erken 1989-2011 (species level). Weekly samples during ice-free period and monthly samples during ice-cover period.

The Erken laboratory is located by the shore of lake Erken, 70 km northeast of Stockholm. A substantial lake measurement program has been running for the last 30 years, which includes manual sampling along with high frequency automatic measurements.

Phytoplankton biomass data from Lake Erken 1989-2011 (species level). Weekly samples during ice-free period and monthly samples during ice-cover period.

The data is free to use, but please inform us, so that we can keep track about the projects that make use of our data.

Data över fytoplanktonbiomassa från sjön Erken 1989-2011 (artnivå). Provtagning varje vecka under isfri period och månadsvis provtagning under istäckt period.

Erkenlaboratoriet är belägen vid stranden av sjön Erken, 70 km nordost om Stockholm. Stationen bedriver sedan ungefär 30 år tillbaka ett omfattande miljöövervakningsprogram av sjön Erken, som inkluderar manuella mätningar och högfrekventa automatiska mätningar.

Data över fytoplanktonbiomassa från sjön Erken 1989-2011 (artnivå). Provtagning varje vecka under isfri period och månadsvis provtagning under istäckt period.

Det är fritt fram att använda data från vårt monitoringprogram, men vi vill att ni som använder data ska informera oss så att vi kan hålla reda på vilka projekt som utnyttjar Erkens monitoringprogram.
Växtplankton i sjön Erken, 1989-2011 - Fytoplanktondata i sjön Erken 1989-2011
Keywords: PHYTOPLANKTON; LAKE/POND; Environmental Sciences; Miljövetenskap; Oceanography, Hydrology and Water Resources; Oceanografi, hydrologi och vattenresurser